A nők családon belüli önrendelkezési jogának és szexuális egyenjogúságának alakulása Németországban a büntetőjogi reformok tükrében 1871-től a 21. század elejéig - Dujic, Dejan (Díké - A Márkus Dezső Összehasonlító Jogtörténeti Kutatócsoport folyóirata, 2023)
The current paper can be seen as a continuation of the presentation on Family Law Workshop IV 2020 (‘The 20th century development of the Bonus et diligens pater familias in the light of the German marriage and family law reform law of 1976 until the existence of the modern family model’), where I approached the development of women’s rights and rights of self-determination on the ground of private law and public law. In the present paper, I attempt to show the evolution of women’s right to self-determination and to bodily self-determination (abortion) on the ground of criminal law. It is important to bear in mind that the positive development of the legal status of German women in family law and public law did not mean that the principle of gender equality in the German criminal law was consistently applied. Many authors see the delay in starting criminal law reforms as a result of the fact that criminal law norms concerning the status of women were influenced by traditional law and a misinterpreted Christian worldview up until the second half of the 1970s. For a long time, sections 177 and 218 of the Penal Code were strictly named as sexual offences, because the issues of sexuality and abortion were treated from the point of view of the sanctity of the family, without questioning the husband’s authority (patria potestas) and position as ‘lord’ of the family in these matters. In the women’s movements, this triggered a revolt not only against the so-called male state, but also against the traditional Christian world, which was accompanied in the second half of the 20th century by a reaction against the ideologically driven, extreme family policies and abortion bans of the National Socialist era. To this day, their main aim is to abolish this male authority and to eradicate the remnants of the male Munt from the legal institutions. This paper will review the results of these efforts from the second half of the 19th century to the beginning of the 21st century.